Some Factors Causing the Delinquency Student in 4th Grade of Primary School Purwodadi - Hermanita (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
The purpose of this study was to determine the factors causing delinquency of 4th Grade students of Primary School Purwodadi , to find out how to deal with delinquency of 4th Grade students of Primary School Purwodadi. This research uses a qualitative approach. This type of research is a qualitative descriptive study, research time in August 2018. Subjects in the study amounted to 35 people consisting of 18 men and 17 women, 4th Grade students of Primary School Purwodadi, Nagan Raya District. Data collection techniques such as: interviews, observation and documentation. Based on the results of the research, the factors causing the delinquency of 4th Grade students of Primary School Purwodadi are the delinquency of students that occurs at school is not only influenced by students' internal factors, but there are also external factors which also greatly affect the delinquency of students and how to handle delinquents of 4th Grade students of Primary School Purwodadi from the solutions provided by the teacher are often spontaneous without regard to the psychological impact of students which consequently can cause problems for students who get sanctions. Like, the teacher punishes students in front of their peers, thus making the students embarrassed, because they are embarrassed that the student won't go to school the next day. This is what is meant by problems for students.